Investigating Oligodendrocyte Biology and Function: Insights from Neurological and Neuromuscular Diseases - Cummings, Sarah (Université d'Ottawa / University of Ottawa, 2020)
Oligodendrocytes (OLs) are the cells responsible for myelin production in the central nervous system (CNS). Myelin serves to increase the efficiency of signal propagation down the axon and is essential for proper communication between the CNS and the periphery. As a result, pathologies affecting the OL, including multiple sclerosis (MS) and multiple system atrophy (MSA), present with a wide range of symptoms including impaired muscle control, loss of coordination, as well as cognitive deficits. While the biology of the OL continues to garner research interest, much remains to be understood about cell function in a healthy context, and also how the biology of these cells goes awry in disease. Our objective was to explore the effects of varying disease models on OL biology and use those findings to further our knowledge on the biology of OL development and regeneration. Here we explore OL function and dysfunction in the context of spinal muscular atrophy (SMA), MSA and MS. We have thoroughly characterized the OL response to SMN-depletion and have determined that SMN is not required for the development of OLs in the neonatal brain. Additionally, we have sought to characterize the endogenous role of MSA-disease relevant protein alpha-synuclein in OL development and have determined that this protein is not required for OL differentiation or CNS myelination. Lastly, we have explored the biology of the OL in the context of the inhibitory milieu it faces during remyelination in MS. We have investigated different pathways that may be involved in mediating signalling of one such inhibitory cue (chondroitin sulphate proteoglycans, CSPGs), and have extended this model to interrogate OL cytoskeletal dynamics in the context of CSPGs. Together, this work uses disease frameworks to investigate basic OL biology, as well as provides insights into how the OL and its interactions with the extracellular milieu should be considered in disease pathogenesis and therapeutic exploration.
Keywords: Oligodendrocyte; Neurodegenerative Disease